PERMINTAAN ANAK : APAKAH ANAK LAKI-LAKI DAN PEREMPUAN MEMILIKI NILAI YANG SAMA? - Dewi Zaini Putri (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2016)
In the last few decades, BKKBN had success with the slogan "two children are enough, men and women are same", but in the lives of people of West Sumatra with the matrilineal system, probably will have its own assessment. Using Poisson and logistic regression analysis obtained (1)  Wife education, age at marriage, age of head of household, spending, business sector head of the household, and home ownership status significantly influence demand for children. (2) Preference sex of the child, the wife  education, age of head of household, wife's employment status and number of children under 5 years significant effect on household desire to have children again. An important finding of this study is a household that already has two children with the same sex have a high tendency to immediately add a child. The implications of this study indicate that the importance of education, especially for women, delaying the age of marriage, and particularly planning sex of the fetus, which is still very rarely carried out in an effort to reduce the level of fertility.Keywords: demand for children;  logistic regression, poisson regression